2017
DOI: 10.1038/bcj.2017.15
|View full text |Cite|
|
Sign up to set email alerts
|

Germline mutations predisposing to diffuse large B-cell lymphoma

Abstract: Genetic studies of diffuse large B-cell lymphomas (DLBCLs) in humans have revealed numerous targets of somatic mutations and an increasing number of potentially relevant germline alterations. The latter often affect genes involved in DNA repair and/or immune function. In general, defects in these genes also predispose to other conditions. Knowledge of these mutations can lead to disease-preventing measures in the patient and relatives thereof. Conceivably, these germline mutations will be taken into account in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 100 publications
1
32
0
1
Order By: Relevance
“…However, expression of low levels of NHEJ proteins such as Ligase IV and KU80 were consistent with compromised NHEJ in DLBCL cells. Consistent to this, previous sequencing studies of DNA DSB repair genes have identified many mutations in c‐NHEJ genes in DLBCL . In a recent study, we observed that although treatment with SCR7, an inhibitor of NHEJ, alone was less sensitive, its combination with radiation resulted in enhanced cytotoxicity in SUDHL8 cells…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, expression of low levels of NHEJ proteins such as Ligase IV and KU80 were consistent with compromised NHEJ in DLBCL cells. Consistent to this, previous sequencing studies of DNA DSB repair genes have identified many mutations in c‐NHEJ genes in DLBCL . In a recent study, we observed that although treatment with SCR7, an inhibitor of NHEJ, alone was less sensitive, its combination with radiation resulted in enhanced cytotoxicity in SUDHL8 cells…”
Section: Discussionsupporting
confidence: 87%
“…Consistent to this, previous sequencing studies of DNA DSB repair genes have identified many mutations in c-NHEJ genes in DLBCL. 22,26,27 In a recent study, we observed that although treatment with SCR7, an inhibitor of NHEJ, alone was less sensitive, its combination with radiation resulted in enhanced cytotoxicity in SUDHL8 cells. 50 Previous studies have suggested that different cancer cells have varying levels of c-NHEJ.…”
Section: C-nhej In Normal Cells Versus Dlbcl Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding of the mechanisms in lymphoma predisposition is limited in people. Using techniques such as targeted sequencing or whole exome/genome sequencing, germline variants in 49 genes have been associated with diffuse large B‐cell lymphoma . Most of these genes are involved in DNA repair or immune function and are suspected to contribute to the pathogenesis of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Using techniques such as targeted sequencing 60 or whole exome/genome sequencing, 61-63 germline variants in 49 genes have been associated with diffuse large B-cell lymphoma. 64 Most of these genes are involved in DNA repair or immune function 60,64 and are suspected to contribute to the pathogenesis of lymphoma. Similarly, knowledge of germline mutation in dogs is limited.…”
Section: Discussionmentioning
confidence: 99%